Walking and Cycling as Modalities of Political Enunciation in Paolo Rumiz’s A piedi (2012 ‘On foot’) and Tre uomini in bicicletta (2002 ‘Three men on their bikes’) - Barbara Siller (Studies in 20th & 21st Century Literature, 2020)
The great number of travel narratives written by Paolo Rumiz from Trieste, Italy, include books about walking and cycling, as well as travelling by train or ferry. On the one hand, these accounts present detailed descriptions of the routes taken on these journeys, depict illustrations of historic buildings, and display various types of maps, and as such, are meant to serve as walking guides (Rumiz 2012, 12). On the other hand, they become a space of reflection for a wide range of themes, including walking slowly as a way to clear your mind, to comfort your heart, and to heal your body, as a form of escape from a rapid and technologized working life, as a revolutionary act against immoderate lifestyles, as a way of regaining one’s own capacity to take note of miracles (Rumiz 2012), with cycling as an alternative form of travelling, a form of existential nomadism, an expression of solitude and slowness, but also as a form of memory and introspection (Rumiz 2002). The following contribution will explore the expressive modalities of walking and cycling in A piedi (2012) and Tre uomini in bicicletta (2002) by Paolo Rumiz by taking into consideration the three values of walking enunciations as outlined by Michel de Certeau, namely, the truth value, the epistemological value, and the ethical value. I will discuss how Rumiz attempts to integrate these three values in his texts, and how the chosen genre – a hybrid between a diary, a historical guide, a walking guide, and a reflective narrative – allows him to combine all three values to a certain extent. In this way, the narrators explicitly address their readership, consequently taking on social and political responsibilities.
Keywords: walking and cycling narratives; expressive modalities; forms of resistance